Developing Interactive Game for Problem Solving Ability of 5-6 Years Kindergarten Children - Srigusmayanti Srigusmayanti; Yaswinda Yaswinda (STAI Hubbulwathan Duri, 2023)
The objective of this study was to develop an interactive game that enhances problem-solving abilities in Kindergarten students aged 5-6 years. This research falls under the category of Research and Development, utilising the Borg Gall developmental paradigm. It implemented 9 out of the 10 developed stages, specifically: 1) Identifying instructional objectives, 2) Instructional analysis, 3) Analysis of learners and context, 4) Formulating performance objectives, 5) Developing assessment instruments, 6) Developing instructional strategies, 7) Developing and selecting teaching materials, 8) Designing and conducting formative evaluation of instructions, 9) Revising instructions. The class exam evaluation revealed that the average score in class B1 was 85.55%, while in class B2, the average score among presenters was 83.77%. The findings from the medium grade exam indicated that interactive games were effective in enhancing problem-solving skills in early infancy.